Comparison of cefepime and ceftazidime in combination with amikacin in the empirical treatment of high-risk patients with febrile neutropenia: A prospective, randomized, multicenter study - KORTEN, VOLKAN (TAYLOR & FRANCIS AS, 2001)
A total of 208 adult patients with cancer and febrile neutropenia from 5 medical institutions were randomized to receive either cefepime (2 g b.i.d.) or ceftazidime (2 g t.i.d.) in combination with amikacin (15 mg/kg/o.d.). Ninety-seven patients in the ceftazidime (CEZ) group and 98 in the cefepime group (CEF) were evaluable for efficacy. In 68 patients (35%), infection could be documented. The average duration of antibiotic therapy was 11 and 12 d and response rates to the empirical regimen were 36 and 30% for the CEZ and CEF groups, respectively (p>0.05). The average time of defervescence in responders was 3 d for both groups. Modification of the initial regimen with antivirals and/or azole antifungals raised the number of responders to 44% and 35%, respectively (p>0.05). Vancomycin was additionally given to 29 patients in the CEZ group and to 27 patients in the CEF group. Twenty-six patients in each group received empirical amphotericin B. Mild, reversible study drug-related side-effects were observed in 12 patients (12%) in the CEZ group and 13 patients (13%) in the CEF group (p>0.05). Cefepime in combination with amikacin seems to be as effective, safe and tolerable as ceftazidime + amikacin in patients with high-risk neutropenia and fever.
Keywords: CANCER-PATIENTS; FEVER; THERAPY; MONOTHERAPY; TRIAL